GENRES OF LITERARY CRITICISM - M.A. Jurayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article covers the genres of literary criticism in detail. In the coverage of the topic, the conclusions of many scientists were used.